The ghost of a chance? Thinking colours across languages and cultures - Lopes, Alexandra (2018)
In 1810, Johann Wolfgang Goethe suggested in Zur Farbenlehre that colour is a phenomenon diffi cult to categorise, resulting as it does from physiology, physics and perception. The fact that colour seems to be experiential to a large extent posits an interesting (and challenging) problem to literary works focussing on it. In this article, I argue that this issue is translational in nature and takes shape at two levels: fi rst, at the level of its representation in literary works — how does one translate a visual experience into words? —, and secondly at the level of its re-representation in translated literary works — how does one translate what is essentially an already-translated visual experience? Whenever colour is semantically and morphologically constitutive of meaning in literature, untranslatability haunts the text. However, publishers and translators rarely shrink from the task of translating on this account. This stake against probability is well worth looking into, as it may uncover a wealth of creativity and a resistance to the understanding of art as solipsism. In this article, Paul Auster’s ‘Ghosts’, part of his New York Trilogy, will be read as a text suggesting a culture-bound hermeneutics of colour, and as such probably untranslatable. I discuss the possible paradox of this degree of untranslatability against the text’s actual ‘translatedness’ by examining the two existing translations into European Portuguese.